Annexation, normalization and the two-state solution in Israel-Palestine - Shemer-Kunz, Yoav (Frontiers in Political Science, 2023)
How Israelis and Palestinians see the conflict between both groups and its eventual solution? Based on 38 in-depth interviews with Israeli and Palestinian political leaders, the article analyzes the Palestinian choice of the two-state solution as the best way to bring an end to the Israeli occupation of 1967. The article then explores the Israeli policy of annexation of the West Bank and the entrenchment of apartheid—a one-state reality of unequal rights from the river to the sea. While the Israeli interviewed attempt to normalize this one-state reality, the Palestinians oppose these attempts of normalization and perceive the emerging debate on the need to reconsider the two-state solution as part of Israel's efforts to normalize the facts on the ground. Finally, the article explores the particular position of the Palestinians in Israel, who were not part of the national project of Palestinian statehood and hence developed their own future vision, based on equal citizenship. The article concludes that more research is needed on this particular group.